Hidden Selectivity: Irregular Migrants and Access to Socio-Health Services in a Heated Local Context - Bracci, Fabio; Valzania, Andrea (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
Irregular migrations and access to social and health services by undocumented migrants has become a very relevant issue in the Italian public discussion about migration policies in the last years. On one hand, the criminalisation of irregular migration has been feeding xenophobic policies; on the other hand, the regional law on immigration in the Region of Tuscany has been trying to put forward an alternative model. By declaring the right of irregular migrants to access basic socio-health services, the Region of Tuscany enacted a radical opposition to the National Immigration Law. In such a context, what happens when irregular migrants meet public services, and in particular, social and health services, in a local area characterised by a significant number of migrants? The following reflections deal with the municipality of Prato: since the end of the 1980s, this city has become the settlement area of a high number of migrants coming from many different countries. The paper underlines both the lack of efficacy of policies merely inspired to repressive goals and the very influential role played by operators within the public sector and non-profit associations in dealing with ambiguous, informal, and unclear domains of intervention. In a context marked by a growing disengagement of the public sector toward marginal and vulnerable people (like, in many cases, irregular migrants), the time has come to impose a new commitment for the public sector and draw a different way of considering the needs of irregular migrants.